Factors governing the prevalence and richness of avian haemosporidian communities within and between temperate mountains. - Juan Carlos Illera; Guillermo López; Laura García-Padilla; Ángel Moreno (PLoS ONE)
Mountains are well-suited systems to disentangle the factors driving distribution of parasites due to their heterogeneity of climatic and habitat conditions. However, the information about the relative importance of environmental factors governing the distribution of avian haemosporidians on temperate mountains is very limited. The main goal of the present study is to identify the factors determining prevalence and richness in avian haemosporidians (Plasmodium, Haemoproteus and Leucocytozoon) at the community level along elevational gradients on two mountain ranges located around the northern and southern limits of the Iberian Peninsula (Spain). We used samples from 68 avian species and 1,460 breeding individuals caught over widespread woodland and open habitats. Our findings confirmed the importance of climatic variables explaining prevalence and richness on Iberian mountains. However, landscape variables and other factors named host richness and migration behaviour explained more variation than climatic ones. Plasmodium genus preferred open and warm habitats. Water sources were also important for the southern but not for the northern mountain. Haemoproteus and Leucocytozoon showed affinities for woodland areas. Climatic conditions for Haemoproteus and Leucocytozoon were dependent on the mountain range suggesting some adaptation of avian haemosporidian and their invertebrate vectors to the climatic particularities of both mountain massifs. In contrast to Plasmodium and Haemoproteus genera, Leucocytozoon prevalence and richness values were significantly higher in the southern mountain range. Overall, our findings at the community level has enriched the relative weight and effect direction of environmental factors governing the distribution and prevalence of the avian haemosporidian community. Also, our results provide a caution message about the precision of predictive models on parasite distributions based on climatic variables, since such predictions could overestimate the effect of climate change scenarios on the transmission of the haemosporidians.